A Study on Primary Health Care Services in the Philippines - Tessa Tan-Torres (Philippine Institute for Development Studies (PIDS), 1995)
From the first part of this paper, results from critical appraisal and description of economic impacts on health policy show that there is a limited expertise in the country on economic evaluation. Despite dissemination, only 25% has an impact on policy. The second part includes the development of self-instructional manual on cost-effectiveness for health center physicians.
Keywords: 330; health sector; health care; hospitals; physician/medical professions; health centers; cost-benefit analysis; family planning; care services